(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
The purpose of the paper is to present a survey on advertisements for jobs in accountancy published at the web site www.moj-posao.net from April 9th until June 1st, 2015. Following characteristics are investigated: employers’ ownership, employers’ trade, employee education and work experience, job type and additional skills. Typical employee in accountancy has a full-time job dominantly in a privately-owned company and an undergraduate or graduate diploma is not always required. People with high school diploma can also apply to many job offers in this sector because the emphasis lies more on the practical skills and a previous working experience is almost always necessary. She or he must know to use at least one accounting computer programme such as Synesis, Pantheon, 4D Wand... Additional skills that she or he should have are analytical skills, eagerness for a life-long learning of countries legislation and International Financial Reporting Standards, interpersonal communication and responsibility. The results of the survey are used to determine the competitiveness of Accounting and Auditing graduates at the Faculty of Economics and Business in Zagreb, Croatia. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.